2000
DOI: 10.1038/sj.onc.1203296
|View full text |Cite
|
Sign up to set email alerts
|

Clustered cysteine residues in the kinase domain of v-Src: critical role for protein stability, cell transformation and sensitivity to herbimycin A

Abstract: We have previously reported the activation of Src by mercuric chloride based on the sulfhydryl modi®cation. To evaluate the signi®cance of cysteine residues in v-Src, we replaced each cysteine to alanine by oligonucleotidedirected mutagenesis and examined its eect on cell transformation. Of ten cysteine residues scattered over vSrc, four cysteines clustered in kinase domain, Cys483, Cys487, Cys496 and Cys498, were important for protein stability and cell transformation, whereas those in SH2 domain were dispens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…They showed that the inactivation was caused by oxidation of Cys 277 , which resulted in homodimerization of c-Src linked by a disulfide bridge. We previously reported the critical role of cysteine residues in the CC motif for the regulation of catalytic activity of c-Src (18). SH-alkylating agents such as BIPM and NAM are known to inhibit kinase activity of v-Src by directly binding to cysteine residues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that the inactivation was caused by oxidation of Cys 277 , which resulted in homodimerization of c-Src linked by a disulfide bridge. We previously reported the critical role of cysteine residues in the CC motif for the regulation of catalytic activity of c-Src (18). SH-alkylating agents such as BIPM and NAM are known to inhibit kinase activity of v-Src by directly binding to cysteine residues.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of amino acids was performed as described previously (18), and each mutation was confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, cysteine 376 of Ret-PTC-1 or its equivalent is most highly conserved in the sequences of various tyrosine kinases, including Ros, Abl, Src, Fms, Fps, HIR, HER, and Lck (Takahashi et al, 1987), suggesting its critical role in the maintenance and up-regulation of the basal level of catalytic activity of Ret and potentially other tyrosine kinases. Correspondingly, cysteine 475 of Lck (Veillette et al, 1993) and cysteine 498 of v-Src (Senga et al, 2000), equivalents of cysteine 376 of Ret-PTC-1, have been shown to be crucial for either catalytic activity or transforming activity of the kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies by Senga et al (2000) identified a number of cysteine residues in Src necessary for the enzymes stability and transformative ability. Giannoni et al (2005) focused on Cys245 and Cys487 which were demonstrated to undergo intramolecular Although these studies support a model whereby Src is activated in response to ROS, data consistent with an inhibitory role for ROS in Src activity has also been proffered by Kemble et al (2009).…”
Section: Discussionmentioning
confidence: 99%